Chebyshev Collocation Method for Parabolic Partial Integrodifferential Equations - M. Sameeh; A. Elsaid (Advances in Mathematical Physics)
An efficient technique for solving parabolic partial integrodifferential equation is presented. This technique is based on Chebyshev polynomials and finite difference method. A priori error estimate for the proposed technique is deduced. Some examples are presented to illustrate the validity and efficiency of the presented method.